DINAMIKA KOMPETENSI PENGADILAN DALAM MENGADILI SENGKETA PERTANAHAN ANTARA PERADILAN UMUM DAN PERADILAN TATA USAHA NEGARA - Ritonga, Francois Geny; Bethesda, Corine R. (Honeste Vivere, 2025)
The rights of Indonesian citizens are protected by law, including the right to own, obtain, and enjoy land ownership rights, both individually and collectively. Over time, conflicts or disputes often arise as a result of the growing needs of society, including land disputes. Land conflicts or disputes can occur and various problems arise, including: the existence of double certificates (overlapping), unlawful acts, ownership disputes, and others. Conflict or dispute resolution can be resolved through non-litigation or litigation. In the case of litigation, the parties often want a resolution through the Court, either the District Court (PN) or the State Administrative Court (PTUN). The Court has the authority to examine and adjudicate its own case, however, in resolving land conflicts or disputes, it can be resolved between these courts, thus creating dynamics in the court's authority in terms of the Court's competence in adjudicating land disputes